Experimental study of bond-slip of GFRP bars in concrete under sustained loads. (1st June 2015) - Vilanova, I.; Baena, M.; Torres, L.; Barris, C.
Abstract: The structural behaviour of reinforced concrete (RC) elements depends heavily on the bond performance between the concrete and the reinforcing material. Bond behaviour under short-term testing has been extensively analysed for steel reinforcement and many studies have been carried out for fibre reinforced polymer (FRP) reinforcement. However, there has only been limited investigation of the long-term effects of this interaction. Several factors can affect the long-term bond behaviour of these elements, the most important being bond length and the immediate and time-dependent properties of reinforcement and concrete (concrete grade, creep, shrinkage and stiffness). This time-dependent behaviour is likely to cause changes and redistributions in bond stresses not properly considered in the limited existing literature. In this experimental study, the bond performance of GFRP RC under sustained load is investigated through pull-out tests. A total of 12 pull-out specimens were tested for a period of between 90 and 130 days. Two concrete strengths (35 MPa and 50 MPa), two bond lengths (5 and 10 times the diameter of the reinforcing bar) and two reinforcing materials (glass fibre reinforced polymer (GFRP) and steel) were used. Experimental results regarding immediate and time-dependent slip are presented and analysed here. In addition, some specimens were instrumented, with internal strain gauges in the reinforcing bar to provide data on the reinforcement strain, thus allowing the distribution of bond stresses and their evolution during sustained loading to be also presented and analysed.